Fluorescence diagnosis of pre-invasive cervical pathology - I. P. Aminodova (Biomedical Photonics, 2015)
Results of local fluorescence spectroscopy in 185 women with underlying and pre-invasive disease of cervix and high-risk HPV infection are represented. Fluorescence study was performed 2h after intravenous injection of fotoditazin in a dose of 1 mg/kg (wavelength 636.5 nm). Accumulation of the photosensitizer was estimated by diagnostic parameter (DP) value, calculated as mean value of fluorescence scaled to each type of tissue. For normal tissues DP accounted for 0.6±0.4, showing accumulation of the photosensitizer. According to the study the medication did not also accumulate in retention cysts (DP 0.3±0.1), explaining low efficiency of photodynamic therapy for this pathology. The accumulation of fotoditazin depends significantly on type of pathologic tissue. In patients with inflammation, leukoplakia and CIN I accumulation of the photosensitizer in pathologic foci was negligible: DP accounted for 1.7±0.2, 1.8±0.2 and 2.1±0.3, respectively. In sites of endometriosis and CIN II DP was significantly higher and accounted for 8.3±2.1 and 14.1±4.1, respectively. The greatest accumulation of the photosensitizer was registered in sites of CIN III, squamous cell carcinoma and adenocarcinoma. Though DP value for these pathologies had almost no difference and accounted for 23.1±4.7, 22.7±1.8 and 23.3±1.4, respectively. For fluorescence diagnosis of severe dysplasia in 48% of patients borders of fluorescence regions were beyond lesions detected for extended colposcopy with additional areas of fluorescence. Targeted biopsy of these regions proved pathology in all patients: CIN II, CIN III, mild dysplasia or CIS. Thus, local spectroscopy allows to diagnosis multifocal lesions on cervix, to define correctly borders of lesion and consider excisional biopsy in-time.